Redesain Pasar Baru Cikarang dengan Konsep Industrial Architecture - Astuti, Retno Fitri; Putri, Isria Miharti Maherni; Soeroso, Yusdianto Haryo; Riyadi, Selamet (Attractive : Innovative Education Journal, 2022)
The market plays a crucial role in driving the economy and catering to the community’s needs. Pasar Baru Cikarang, located in the Bekasi Regency, serves as a significant market for the Cikarang area. Historically, Pasar Baru Cikarang was an impressive market that underwent construction and renovation in 1992, was completed in 1994, and commenced operations in 1995. However, the occurrence of looting events resulted in many traders resorting to street vending, leading to a decline in the market's appearance, which now appears shabby and untidy. This disrepair negatively impacts the primary area of Bekasi Regency, especially Cikarang, an ASEAN Industrial City. Considering the importance of having an architectural icon for an industrial city, the concept of industrial architecture becomes crucial. Industrial architecture embraces a minimalistic approach to final building finishing, making it an ideal choice for market buildings. Implementing this architectural concept in Pasar Baru Cikarang could revitalize the market's fading image and transform it into an iconic representation of the Industrial City. By emphasizing the industrial architecture concept in the renovation of Pasar Baru Cikarang, it is anticipated that the market's overall appeal will be enhanced, providing a boost to the local economy and reinstating its significance as a vital hub for the Cikarang area. This revitalization project can also contribute to the city's identity, further strengthening its position as an ASEAN Industrial City. Keywords: Cikarang Regency, Industrial City, Industrial Architecture